Fiscal Deficit, National Saving and Sustainability of Economic Growth in Emerging Economies: A Dynamic GMM Panel Data Approach - Antonino, Buscemi; Alem, Yallwe Hagos (International Journal of Economics and Financial Issues, 2012)
The neoclassical growth models argued that the movement to steady states; technology, exogenous rate of savings, population growth and technical progress stimulate higher growth levels (Solow 1956). Contrary to the neoclassical argument, endogenous growth model argues that, in the theory of endogenous growth, government play a significant role in promoting accumulation of knowledge, research and development, public investment, human capital development, law and order can generate growth both in the short and long run. Moreover, they assumed technical progress as endogenous variable for growth (Barro 1995). This study analyze the effects of fiscal deficit on sustainability of economic growth and provided new empirical evidence on the effects of fiscal deficit on saving and sustainability of economic growth based on the assumption of endogenous growth model. We estimated using the reduced form of GMM method for dynamic panels covers 1990-2009 for three emerging countries that includes China, India and South Africa. Keywords: Fiscal deficit; National saving; Sustainability; Growth. JEL Classification: C33; C 61; E62; O16; O47